The spectrum of brain malformations and disruptions in twins. Issue 9 (18th November 2020) - Park, Kaylee B.; Chapman, Teresa; Aldinger, Kimberly A.; Mirzaa, Ghayda M.; Zeiger, Jordan; Beck, Anita; Glass, Ian A.; Hevner, Robert F.; Jansen, Anna C.; Marshall, Desiree A.; Oegema, Renske; Parrini, Elena; et al.
Abstract: Twins have an increased risk for congenital malformations and disruptions, including defects in brain morphogenesis. We analyzed data on brain imaging, zygosity, sex, and fetal demise in 56 proband twins and 7 less affected co‐twins with abnormal brain imaging and compared them to population‐based data and to a literature series. We separated our series into malformations of cortical development (MCD, N  = 39), cerebellar malformations without MCD ( N  = 13), and brain disruptions ( N  = 11). The MCD group included 37/39 (95%) with polymicrogyria (PMG), 8/39 (21%) with pia‐ependymal clefts (schizencephaly), and 15/39 (38%) with periventricular nodular heterotopia (PNH) including 2 with PNH but not PMG. Cerebellar malformations were found in 19 individuals including 13 with a cerebellar malformation only and another 6 with cerebellar malformation and MCD. The pattern varied from diffuse cerebellar hypoplasia to classic Dandy–Walker malformation. Brain disruptions were seen in 11 individuals with hydranencephaly, porencephaly, or white matter loss without cysts. Our series included an expected statistically significant excess of monozygotic (MZ) twin pairs (22/41 MZ, 54%) compared to population data (482/1448 MZ, 33.3%; p  = .0110), and an unexpected statistically significant excess of dizygotic (DZ) twins (19/41, 46%) compared to the literature cohort (1/46 DZ, 2%; p  < .0001. Recurrent association with twin–twin transfusion syndrome, intrauterine growth retardation, and other prenatal factors support disruption of vascular perfusion as the most likely unifying cause.